Stabilization of physical-mechanical characteristics of honeycomb filler based on the adjustment of technological techniques for its fabrication - Kondratiev, Andrii; Prontsevych, Oksana (Eastern-European Journal of Enterprise Technologies, 2018)
Objective preconditions for a more effective application of honeycomb structures in a number of industries are not only their advantages, already implemented and proven, but also resolving some of their problems. Regardless whether the honeycomb filler is made directly at an enterprise or purchased before forming a structure, it is subjected to various technological operations. In the course of these operations, some of its geometrical parameters undergo change, which is also related to its physical-mechanical characteristics. The paper reports a study into ensuring the physical-mechanical characteristics of honeycomb fillers in the cases when its characteristics are beyond the limits of permissible values due to certain deviations in the geometry of honeycombs, which are to be purposefully adjusted in the process of fabrication of a given material. Based on the conditions for the strength of honeycomb filler in terms of the uniform detachment during stretching a honeycomb packet into a block, we have adjusted its physical-mechanical characteristics by ensuring the regulated range of the honeycomb’s cell stretching angle within the limit of the assigned region of its shape change coefficients. We have obtained the regulated relationship between technological parameters and the honeycomb packet stretching angle and a shape change coefficient. The dependence makes it possible to determine the required range of technological parameters for implementing the physical-mechanical characteristics of honeycomb filler, required by the standard, with the predefined input geometrical parameters of its cell. We have analyzed all existing technological techniques for applying glue bands on a honeycomb filler’s material based on the relation between the step of applying the bands, the cell shape change coefficient, and the dimension of its side. The results obtained make it possible to improve the standard production processes for honeycomb fabrication, which in turn will increase the stability of physical-mechanical characteristics of the honeycomb filler, as well as the structures based on it.